(untitled) (Revista Inclusiones, 2020)
The increasing attention to the concept of a business model is due to a combination of two main factors that have emerged in recent years and have radically changed the competitive landscape. First, the advent of the digital era and new information and communication technologies have disrupted traditional business methods and revealed new paths to value creation. Second, dynamic and globalized markets are forcing companies to rethink and improve their business practices. Nevertheless, there is still no consensus in the scientific world about the concept and essence of a business model, as well as its role in the development of innovation within businesses. In this regard, the purpose of this study is to define the concept and classification of a business model to understand the essence of a business model, as well as to consider its role in stimulating innovation within businesses. The authors used a literature review method as the research method for this work. The research has revealed that the scientific community has not yet formed a single viewpoint on the essence of a business model. Most authors use the term "mechanism" or "method" of doing business as a base. However, the term still does not have a generally accepted concept. There are several classifications of business models. The literature review also showed an underdeveloped scientific discourse on the topic of business model innovation.